Titanium Alloy Fabricated by Additive Manufacturing for Medical Applications: Obtaining, Characterization and Application—Review - Xinjie Zhang; Shuai Liu; Yude Liu; Hanjie Guo; Wentian Shi (Metals, 2023)
Metal additive manufacturing (metal-AM) technology has made significant progress in the field of biomedicine in recent years. Originally, it was only used as an innovative resource for prototypes. With the development of technology, custom orthopedic implants could be produced for different patients. Titanium alloy is non-toxic and harmless in the human body. It has excellent biocompatibility and can promote the growth and regeneration of bones in its interior. Therefore, it is widely used in the medical industry. However, in the process of additive manufacturing and printing titanium alloys, there are often cases where the powder is not completely melted or the powder adheres to the product structure after printing, which introduces new biological risks. This paper summarizes the causes of powder adhesion from the perspective of the process involved in additive manufacturing, expounds the influence of different processes on the powder adhesion of titanium alloy forming parts, introduces the mainstream methods of powder sticking removal and summarizes the application of the additive manufacturing of titanium alloy in the medical field, which provides a theoretical basis for further development of the application of titanium alloy additive manufacturing technology in the medical industry.